ON SOME PROPERTIES OF THE PARAMETRIC FORM LAPLACE TRANSFORMATIONS - Shevelev , A. G. (Problems of Informatization and Management, 2021)
The proof of some important theorems for the parametric form of the Laplace transform is given and the application of these theorems for the determination of images and originals of solutions of linear differential equations with variable coefficients and in the analysis of nonstationary dynamical systems is considered.